Long-Term Sequelae in the Respiratory System in Patients Who Were in Intensive Care Units for COVID-19 in a High Complexity Clinic in Neiva, Colombia (2020-2021) - Sergio Julián Perdomo Reyes; Diana Cecilia Mojomboy Palechor; Valentina Pastrana Trujillo; Dayana Valentina Rodríguez Martínez (International Journal of Medical Toxicology and Legal Medicine, 2024)
Care Units (ICUs) required hospitalization, particularly in those who overcame the acute phase but developed long-term respiratory sequelae. This descriptive and retrospective study aims to identify and analyze persistent respiratory sequelae in patients who were hospitalized in a high-complexity clinic in Neiva, Colombia, during the years 2020 and 2021. Based on the review of 285 medical records, it was observed that 72.2% of the patients presented some respiratory sequelae, with dyspnea (45.6%) and pulmonary fibrosis (24.9%) being the most prevalent. A strong relationship was found between the length of stay in the ICU, prolonged use of mechanical ventilation and the development of pulmonary fibrosis. Likewise, pre-existing comorbidities, such as hypertension and diabetes, were significant risk factors for the development of sequelae. The results underscore the urgent need to implement pulmonary rehabilitation programs and long-term follow-up in post-COVID-19 patients to mitigate the effects of sequelae and improve quality of life. This study provides an important overview of the situation in an understudied region and contributes to the growing body of literature on the respiratory sequelae of COVID-19 in critical care settings.